Pengembangan Video Interaktif Tema Selalu Berhemat Energi Untuk Mengetahui Kemampuan Literasi SD NU Sleman Yogyakarta - Syafriza, Azizatul Alif; Mustamid, Mustamid; Kusumastutik, Novi (Universitas Muhammadiyah Magelang, 2022)
Research on the development of interactive video learning media with the theme Always Save Energy was carried out based on the needs of SD NU Sleman which requires interesting media to support students' literacy needs. The research was conducted with the aim of developing interactive video learning media with the theme of always saving energy, knowing the literacy skills of students in class IV through interactive video learning media, and testing the feasibility level of the resulting media. The type of research in this research is development or Research and Development using the 4-D model, which consists of define, design, develop, and disseminate. The population in the study amounted to 66 people. The research instrument used to determine the feasibility of the media used media and language validation sheets which were carried out for 3 class teachers. The instrument used to determine students' literacy skills used questionnaires filled in by students after completing activities on learning media and questions contained in the game. The data analysis technique in this study was seen from the average feasibility score in terms of material and media, which was 85.75%, which was very feasible. While the literacy analysis is seen from the scores of students' literacy questionnaires. The mean value of the literacy questionnaire was obtained at 93.7%, which is in the very good category. This study concluded that interactive video learning media with the theme of always saving energy is very suitable for use in the learning process and is proven to be able to improve students' literacy skills. Interactive video learning media encourages students to be more enthusiastic in learning the content of the material and is able to improve literacy skills in terms of reading instructions as well as reading material. Interactive video learning media encourages students to better understand the learning material as seen from the test results in the game